(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The emergence of social media has reshaped various aspects of society, including the empowerment of women in India. This paper explores how platforms like Facebook, Twitter, Instagram, YouTube, and WhatsApp have contributed to advancing women's rights, offering them a voice, and challenging traditional gender roles. By analyzing various case studies, challenges, and opportunities, this paper demonstrates how social media acts as a tool for fostering change and promoting women's empowerment in India.